Treatment of hyperemesis gravidarum accompanied by metabolic disorders by modified Liujunzi decoction, acupressure combined with rehydration - Xiaobei Zhong
We aimed to assess the therapeutic effects of modified Liujunzi decoction, acupressure combined with rehydration on hyperemesis gravidarum (HG) (spleen and stomach weakness syndrome) accompanied by metabolic disorders. Two hundred pregnant women admitted from January 2019 to June 2022 were divided into an observation group (n=100) and a control group (n=100) using a random number table. The control group was given rehydration, on the basis of which modified Liujunzi decoction and acupressure were utilized for the observation group. Both groups were treated for 7 d. The total effective rate was higher in the observation group than that in the control group. Blood potassium and sodium levels increased in both groups after treatment, which were higher in the observation group (p<0.05). The observation group had a higher negative conversion rate of urinary ketone body than that of the control group (p<0.05). The scores of physical symptoms and worsening factors, fatigue, mood and restriction as well as total score of Nausea and Vomiting of Pregnancy Quality of Life decreased in both groups after treatment, which were lower in the observation group (p<0.05). No adverse reactions occurred in the control group during treatment, while 1 case of skin allergy and 1 case of stomach distension occurred in the observation group. Modified Liujunzi decoction, acupressure combined with rehydration can effectively and safely restore the electrolyte balance, shorten the time to recovery, alleviate the clinical symptoms and improve the quality of life of patients with HG accompanied by metabolic disorders.